The Course of Grieving for Different Types of Losses in War: "Phoenix" Research Project Protocol: Experience in Implementing Respondent Engagement - Leshchuk, Ірина; Frankova, Ірина; But, Тетяна; Norkina, Ірина; Haustova, Олена; Chaban, Олег; Mukharovska, Інна; Zelenko, Єлизавета; Sak, Леся (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online. Abstract. The topic of grief after the loss of a loved one becomes especially relevant in times of war. New revisions of the classifications used in psychiatry contain codes for both normal and pathological grief. However, the diagnostic criteria in different classifications are slightly different. Therefore, it is important to study the course of grief in the context of war realities. The abstract presents a research protocol for studying the course of grief after the loss of a loved one in the context of wartime, describes the challenges during the process of engaging respondents and ways to solve them by the research team.